A milestone for Pentatomoidea: Grazia et al. 2008—What do we know and where can we go? - Bianchi, Filipe Michels; Barão, Kim Ribeiro; Grassi, Augusto; Ferrari, Augusto (Zootaxa, 2021)
Pentatomoidea is the third largest superfamily in Heteroptera. The internal systematics and classification of this superfamily have an intricate history. The paper by Grazia et al. (2008) is a milestone to the phylogenetic hypothesis of Pentatomoidea. Subsequent papers explored the limited conclusions and unanswered questions left by Grazia et al. (2008). We proposed to look at the body of knowledge produced since Grazia et al. (2008) and to compile the molecular data for Pentatomoidea deposited in Genbank to achieve three aims: (i) to evaluate the advances on the phylogenetic relationships of the Pentatomoidea; (ii) to produce a phylogenetic hypothesis based on molecular data deposited in Genbank; and (iii) to highlight the shortcomings and strengths of the available data. We retrieved sequences of four molecular markers (COI, 16S, 18S, and 28S) for 167 terminal taxa, including 149 pentatomoids. A concatenated matrix was analyzed under maximum likelihood (ML) and parsimony (MP). Both methods supported the monophyly of Pentatomoidea, and poorly resolved internal relationships among the families. Acanthosomatidae, Dinidordae, Pentatomidae, Scutelleridae, Thaumastellidae, and Urostylididae were monophyletic (under ML and MP), and also Plataspidae and Thyreocoridae (under ML). Tessaratomidae and Cydnidae were non-monophyletic under both methods. Our results were compared to the phylogenetic hypotheses proposed for Pentatomoidea. The analysis of the data available on the GenBank allowed us to affirm that many problems mentioned previously remain unsolved, even though the sampling of terminals has increased. In summary, the efforts in the last two decades to better understand the relationships within the Pentatomoidea have been insufficient to propose robust advances in phylogenetic hypothesis for the group. We discuss topics we understand are paramount to upcoming developments:1) better taxon sample; 2) collection management; 3) increased markers; and 4) morphology and anatomical ontology.